A skill profile of elite Iranian greco-roman wrestlers - Mirzaei, B.; Akbar Nezhad, A. (World Journal of Sport Sciences, 2008)
The aim of this study was to make a skill profile of elite Iranian Greco-roman wrestlers. For this purpose, five relevant techniques in 141 wrestlers in two separate groups were assessed (junior n = 71 and senior n = 70). Scoring method for each technique was filmed and reviewed in a non-competitive situation. The results showed that Iranian Greco-roman wrestlers earned high scores in all five techniques in both junior and senior groups.